POLA PENDIDIKAN AGAMA ISLAM PADA ANAK KORBAN KELUARGA BROKEN HOME - Qurrota A’yuni; Syafira Maharany; Nonik Kasiari; Wildani Firdaus (IMTIYAZ: Jurnal Ilmu Keislaman, 2021)
Marriage is the first step in forming a family. The expected family is, of course, a family filled with harmony with the presence of children who become jewelry and conditioning the hearts of all parents. The emergence of rifts and friction in the family is commonplace. However, the level of ability of each person is different. A harmonious family to old age is the result of his efforts in maintaining and maintaining relationships. On the other hand, when a family is damaged which leads to divorce, it is a failure to maintain relationships. In this case, the main party who is harmed is the child. Where he had to experience many changes in his life, especially from the social-emotional side. However, all problems must have a solution. Likewise for children who are victims of broken homes, both parents, neighbors, friends and teachers have their respective roles in how to deal with and treat children who are victims of a broken home. But basically it is parents who have an important and mosttimportant role in determining the fate  of youngsters. The family is a madrasa for their children